Luescher, T.M., Webbstock, D. & Bhengu, N. (Eds.) (2020). Reflections of South African Student Leaders, 1994 to 2017. Cape Town, South Africa: African Minds. (Journal of Student Affairs in Africa, 2021)
Animated by the voices of 12 former student leaders representing Students' Representative Councils (SRCs) from a few public universities across the country, Reflections of South African Student Leaders, 1994 to 2017 situates the discourse-shifting #RhodesMustFall and #FeesMustFall movements as an inevitable progression after two decades of governmental and institutional shillyshallying on urgent issues confronting the progressively diverse national student body.